Assessment of the nocturnal boundary layer height based on long-term atmospheric radon measurements - Kubiak, Joanna Aleksandra; Zimnoch, Miroslaw (Frontiers in Earth Science, 2022)
The article presents the results of statistical analyzes of meteorological and atmospheric radon concentration measurements carried out in Krakow in the years 2004 to 2013. Based on the diurnal variability, an estimation of the height of the nocturnal boundary layer (NBL) was performed and compared with the ERA5 data. The average concentration of radon in the air of that period in Kraków was equal to (5.262±0.017) Bqm- 3. The diurnal and seasonal variability of radon concentration was found. The correlation of pollution and meteorological parameters calculated based on hourly mean data was analyzed. The correlations obtained were statistically significant, for wind speed (r= -0.38, p<0.001), and air humidity (r=0.33, p<0.001). The possibility of determining of the nocturnal boundary layer height on the basis of radon measurements has been confirmed; however, the calculation model needs to be refined.